PRIME MINISTER IN FRENCH-SPEAKING BLACK AFRICA. Comparative analysis from examples of Togo and Ivory Coast. - (:unkn) unknown (My University, 2021)
The states of French-speaking Black Africa formally broke with the autocratic regimes and the personalization of power that ensued in the early 1990s. Indeed, on this occasion the democratic turn taken by these states led them to adopt fundamental texts establishing , At least formally, the rule of law and modern political regimes.The Constitutions democratically adopted in the early 1990s in the Francophone Black African states, far from reflecting an African originality, were therefore in conformity with the democratic ideals of Western and especially French, constituting only a mimicry of the French Constitution of the Fifth Republic. Indeed, with the notable exception of Benin, which has adopted a political regime oriented towards the American presidential regime, the other states of the French bosom have endeavored to mimic the French model associating presidentialism and parliamentarism.Embodying the unshakable executive power up to then, the President of the Republic is constrained in neo-constitutionalism to share his powers with the Prime Minister, who is one of the innovative figures of the democratic renewal. It was for the constituents to draw lessons from the absolutist conception of the power with which they wanted to break, to establish institutions guaranteeing the balance and separation of powers.While the Constitutions have been in charge of resolving the issue of the division of powers between the President of the Republic, which remains the keystone of the executive power, and the Prime Minister has difficulty in political existence, Expressing much more in the administrative role that the Constitution recognizes. Twenty years after the beginning of the democratic renewal, we propose to carry out a comparative analysis of the evolution of the position of the Prime Minister in the political systems and the implementation of his political and administrative responsibilities in three French-speaking states of Black Africa, namely Togo,
Keywords: African Research